Clinical-pathological features and muscle imaging findings in 36 Chinese patients with rimmed vacuolar myopathies: case series study and review of literature - Wei, Xiao-jing; Sun, Hui; Miao, Jing; Qiu, Ru-qing; Jiang, Zong-zhi; Ma, Zhen-wei; Sun, Wei; Yu, Xue-fan (Frontiers in Neurology, 2023)
Introduction: Rimmed vacuolar myopathies (RVM) are a group of genetically heterogeneous diseases that share histopathological characteristics on muscle biopsy, including the aberrant accumulation of autophagic vacuoles. However, the presence of noncoding sequences and structural mutations, some of which remain undetectable, confound the identification of pathogenic mutations responsible for RVM. Therefore, we assessed the clinical profiles and muscles magnetic resonance imaging (MRI) changes in 36 Chinese patients with RVM, emphasizing the role of muscle MRI in disease identification and differential diagnosis to propose a comprehensive literature-based imaging pattern to facilitate improved diagnostic workup. Methods: All patients presented with rimmed vacuoles with varying degrees of muscular dystrophic changes and underwent a comprehensive evaluation using clinical, morphological, muscle MRI and molecular genetic analysis. We assessed muscle changes in the Chinese RVM and provided an overview of the RVM, focusing on the patterns of muscle involvement on MRI. Results: Thirty-six patients, including 24 with confirmed distal myopathy and 12 with limb girdle phenotype, had autophagic vacuoles with RVM. Hierarchical clustering of patients according to the predominant effect of the distal or proximal lower limbs revealed that most patients with RVM could be distinguished. GNE myopathy was the most prevalent form of RVM observed in this study. Moreover, MRI helped identify the causative genes in some diseases (e.g., Desminopathy, Hereditary myopathy with early respiratory failure) and confirmed the pathogenicity of novel mutation (e.g., adult-onset proximal rimmed vacuolar titinopathy) detected using next-generation sequencing. Discussion: Collectively, our findings expand our knowledge of the genetic spectrum of RVM in China and suggest that muscle imaging should be an integral part of assisting genetic testing and avoiding misdiagnosis in the diagnostic workup of RVM.